Pembelajaran PAKBP dengan Metode PBL Berbantuan E-LKPD sebagai Upaya Peningkatan Bernalar Kritis Fase C Kelas 6 SD Katolik Santa Maria 1 Malang - Whanarian Mukti Cahyo; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The learning method applied in the 6th grade at SD Katolik Santa Maria 1 Malang is still lacking in variety, resulting in a low level of critical thinking among students and the failure to meet the target outcomes in the proficient and skilled categories. This study aims to improve the critical thinking character dimension and achieve target outcomes through the implementation of the Problem Based Learning (PBL) method supported by E-LKPD. This classroom action research was conducted in two cycles with the material "God's Work through the Prophet Elijah," focusing on the sub-topics of Elijah's obedience, God's miracles through Elijah, modern-day idolatry, and the application of Elijah's messages. Each cycle consisted of four stages: planning, action, observation, and reflection. The research subjects were 28 students in the 6th grade, Phase C, at SD Katolik Santa Maria 1 Malang. The research indicators included asking questions, answering questions, comparing various sources of information, increasing personal knowledge, seeking information independently, gathering information from various sources, clarifying information from different sources, comparing information from different sources, selecting information from various sources, and clarifying information with adult guidance. The research results showed that the PBL method was able to enhance the critical thinking dimension of the Pancasila Student Profile (P3) character. The critical thinking dimension's average score increased from 69% to 89%. The PBL method also improved student’s achievement in the material on "God's Work through the Prophet Elijah" in the 6th grade, Phase C, at SD Katolik Santa Maria 1 Malang, showing an increase from 29% proficient, 21% skilled, 43% competent, and 7% developing to 75% proficient, 25% skilled, and 0% in the competent and developing categories. Overall, focusing on the critical thinking dimension through the PBL method with the support of E-LKPD proved to be effective in improving both critical reasoning and academic performance in Catholic Religious Education in the 6th grade at SD Katolik Santa Maria 1 Malang. It is recommended to focus on one dimension by selecting an engaging and activating learning method.